Orthomosaics and digital elevation model of the 'Bear Trap' - a Norse ruin in Northwest Greenland - Carlson, Daniel; Walsh, Matthew J.; Tesjner, Pelle; Thomsen, Steffen (Zenodo, 2020)
This dataset consists of a digital elevation model (DEM) and an orthomosaic of the ‘Bear Trap’ (also called ‘Bjørnefælden’ in Danish, and ‘Putdlagssuaq’ or ‘The Great Trap’ Greenlandic Kalaallisut), a Norse ruin at the western end of the Nuussuaq Peninsula in NW Greenland. Images comprise 1032 low-altitude aerial images acquired from an unoccupied aerial vehicle (DJI Phantom 3 Standard). These images were processed using Agisoft Metashape Pro (v1.7; Linux Ubuntu) following the USGS protocols for processing imagery in coastal areas. The locations of 8 ground control points (GCPs) were surveyed with a high accuracy global navigation satellite system (GNSS) receiver (Emlid Reach). The base station and rover data were processed using the Emlid distribution of the free RTKLib software (https://docs.emlid.com/reach/common/tutorials/gps-post-processing/). Geoid height was computed using the online UNAVCO Geoid Height Calculator (https://www.unavco.org/software/geodetic-utilities/geoid-height-calculator/geoid-height-calculator.html). During the image alignment step in Metashape, the ‘High’ accuracy setting and key point and tie point limits of 60000 and 0 were used. Generic and reference preselection were not used. Gradual selection was used to remove tie points that exceeded thresholds for the projection accuracy, reconstruction uncertainty, and reprojection error and the intrinsic camera parameters were computed for each camera calibration group. GCPs were then imported and placed in each image. The dense point cloud was then computed using the ‘Ultra High’ quality setting, followed by the DEM and orthomosaic. The resolution of the orthomosaic is 1.83 cm/pixel. 5 cm resolution orthomosaic and DEM were also exported for use in QGIS. A complete file list is provided in the README file that accompanies this dataset. The image survey was conducted as part of the Vaigat Iceberg-Microbial Oil Degradation and Archaeological Heritage Investigation (VIMOA) project, which was funded by the Danish Centre for Marine Research and supported by the Arctic Research Centre at Aarhus University, in affiliation with the National Museum of Denmark, the Greenland Institute of Natural Resources, and The Greenland National Museum and Archives in Nuuk. Proper archaeological permits for the survey were obtained in advance from the Greenland National Museum and Archives in Nuuk. Walsh et al. (2020) provide an overview of the archaeological surveys conducted during the VIMOA project and Walsh et al. (in prep) provide further details specific to The Bear Trap and surrounding archaeological contexts observed during the 2019 survey. Walsh et al. (2020) The VIMOA project and archaeological heritage in the Nuussuaq Peninsula of north-west Greenland. Antiquity 94:e6 doi:10.15184/aqy.2019.230 Walsh, Matthew J., Daniel F. Carlson, Pelle Tejsner, and Steffen Thomsen. The Bear Trap: Reinvestigating a unique stone structure on the northwest tip of the Nuussuaq Peninsula, Greenland. Submitted to Arctic Anthropology .